2019
DOI: 10.1186/s40813-019-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunocrit, serum amino acid concentrations and growth performance in light and heavy piglets depending on sow’s farrowing system

Abstract: Background The conventional farrowing crate is criticised due to the limited mobility of sows during farrowing and lactation. The present study aims to investigate the effects of three different farrowing systems on the performance of suckling neonates on the basis of immunocrit (IC; a quantification of immunoglobulins), serum amino acid (AA) concentrations and growth performance. Methods From a total of 149 sows placed in three housing systems (farrowing crate – FC, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Our results did not show any significant difference in piglet serum immunoglobulins between S and L piglets at birth or over time. Conversely, Schnier et al [ 32 ] reported numerically lower immunocrit values in S piglets compared to L piglets. On the other hand, Morton et al [ 33 ] reported that piglet birth weight did not affect serum immunocrit values, which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not show any significant difference in piglet serum immunoglobulins between S and L piglets at birth or over time. Conversely, Schnier et al [ 32 ] reported numerically lower immunocrit values in S piglets compared to L piglets. On the other hand, Morton et al [ 33 ] reported that piglet birth weight did not affect serum immunocrit values, which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The selection was focussed on clinical variables that can be assessed easily by farmers and resulted in body weight, rectal temperature, crown-rump-length, a vitality score and an IUGR score. As clinical variables are often estimated being “subjective” compared to “objective” laboratory parameter, additionally a set of laboratory measurements was selected, expected to be appropriate in predicting the death of a newborn piglet [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection was focussed on clinical variables that can be assessed easily by farmers and resulted in body weight, rectal temperature, crown-rump-length, a vitality score and an IUGR score. As clinical variables are often estimated being "subjective" compared to "objective" laboratory parameter, additionally a set of laboratory measurements was selected, expected to be appropriate in predicting the death of a new-born piglet (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%